Inhibition of Human and Animal Platelet Adhesiveness to Glass Bead Columns by Adenosine, Dipyridamole, Chlorpromazine and Acetylsalicylic Acid - Fujttani, Buichi; Tsuboi, Toshimichi; Takeno, Kazuko; Yoshida, Kouichi; Shimizu, Masanao (Thrombosis and Haemostasis, 1976)
The differences among human, rabbit and guinea-pig platelet adhesiveness as for inhibitions by adenosine, dipyridamole, chlorpromazine and acetylsalicylic acid are described, and the influence of measurement conditions on platelet adhesiveness is also reported. Platelet adhesiveness of human and animal species decreased with an increase of heparin concentrations and an increase of flow rate of blood passing through a glass bead column. Human and rabbit platelet adhesiveness was inhibited in vitro by adenosine, dipyridamole and chlorpromazine, but not by acetylsalicylic acid. On the other hand, guinea-pig platelet adhesiveness was inhibited by the four drugs including acetylsalicylic acid. In in vivo study, adenosine, dipyridamole and chlorpromazine inhibited platelet adhesiveness in rabbits and guinea-pigs. Acetylsalicylic acid showed the inhibitory effect in guinea-pigs, but not in rabbits.